Identification of hijaiyah letters using wirelessly controlled Arabic braille module - Nik Mohd Rahimi, Nik Azimah Zainab; Mohamad Hanif, Noor Hazrin Hany; Janin, Zuriati (Institute of Advanced Engineering & Science, 2020)
Among the major issues faced by the visually impaired people is the inability to read, and this is could be addressed by learning braille. However the scarcity of skilled instructors to teach the braille codes to the visually impaired people limits the learning process. This paper presents a psychophysical study on the ability of people with visual challenges to identify hijaiyah letters from a specially developed Arabic braille module. This module consists of six miniature solenoids that are wirelessly controlled via a Bluetooth and an Arduino Uno microcontroller. Five different hijaiyah letters were provided to the participants and were randomly repeated for three times. The participants were required to touch the Arabic braille module and state the hijaiyah letters that were displayed. With priori knowledge and initial familiarization of the braille patterns, 72.9% of the trials showed accuracy between the braille display and the stated hijaiyah letters. 20% of the participants have the highest repeatability responses of 80%. The outcome of this work showed the optimistic capability of the wirelessly controlled Arabic braille display to assist visually impaired individual to read hijaiyah braille letters and ultimately promotes independence in learning.